2017
DOI: 10.1016/j.ejvs.2017.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Five Year Natural History of Screening Detected Sub-Aneurysms and Abdominal Aortic Aneurysms in 70 Year Old Women and Systematic Review of Repair Rate in Women

Abstract: Screening detected AAAs and sub-aneurysms are clinically relevant in women. Within 5 years of detection a high proportion of AAAs require elective surgery, and a high proportion of sub-aneurysms progress to AAAs. Consequently, surveillance of sub-aneurysms in women with reasonable life expectancy can be considered. Publications on repair rate in women with intact AAAs are scarce and heterogeneous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Two reviewers evaluated 3946 citations and 137 full-text articles against inclusion criteria, and 33 studies (69 articles) met inclusion criteria for this systematic review (Figure 2). Nine new studies were included (4 RCTs, 2 cohort studies, and 3 registry studies) and 24 studies (13 RCTs, 8 cohort studies, 1 case-control study, and 2 registry studies) were carried forward from the previous USPSTF report.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two reviewers evaluated 3946 citations and 137 full-text articles against inclusion criteria, and 33 studies (69 articles) met inclusion criteria for this systematic review (Figure 2). Nine new studies were included (4 RCTs, 2 cohort studies, and 3 registry studies) and 24 studies (13 RCTs, 8 cohort studies, 1 case-control study, and 2 registry studies) were carried forward from the previous USPSTF report.…”
Section: Resultsmentioning
confidence: 99%
“…No trial-level evidence examined the effectiveness of 1-time screening plus rescreening compared with 1-time screening alone. Seven cohort studies (5 fair-quality, 2 good-quality) and 1 fair-quality case-control study recruited screen-negative participants (AAA diameter 2.5-2.9 cm or 2.6-2.9 cm, <2.5 cm, or ≤3 cm) and administered various rescreening protocols (rescreening every 1 to 5 years with 1 to 6 repeated scans), reporting the proportion of initially screen-negative aortas that reached 5.0 or 5.5 cm at the repeat scan (eTables 2 and 3 in the Supplement). This group of heterogeneous studies reported that AAA-related mortality over 5 to 12 years was rare (<3%) among participants with normal aortas (<3 cm) on the initial scan.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those with aortas between 2.5 cm and 2.9 cm were booked for a 5-year follow-up aortic ultrasound scan at their regional hospital vascular unit. The long-term clinical benefit of surveillance in this ‘sub-aneurysmal’ group is unknown but some studies have demonstrated a significant proportion will become aneurysmal within 5 years 22 . Women diagnosed with an AAA from 3.0–5.4 cm were offered cardiovascular risk factor modification advice, provided with an appointment with the local vascular unit for clinical assessment, and entered into follow-up with the local vascular surgery service.…”
Section: Methodsmentioning
confidence: 99%
“…53 The debate extends to follow-up of women with sub-aneurysmal aortas, in whom an equally high proportion will go on to reach threshold for surgery. 54 Current uptake in screening is approximately 80% in the NAAASP, with regular review to improve access and coverage. Turn down rates during the Chichester trial were higher in the older age group (33.8% for subjects aged 76-80 years vs 19.5% for those aged 65 years).…”
Section: Challenges and Controversiesmentioning
confidence: 99%